Environmental Ethics in the Perspective of the Qur'an: Analysis of Surah Al-A'raf Verses 56-58 - Aripin, Ahmad; Nugroho, Kharis (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
This research explores diverse environmen damage problems arising from natural factors and human activities. The qur'an, Especially surah Al-A'raf ; 56-58, discusses environmental learning comprehensiveness. Islamic education is the main means of conveying the importance of caring for the environment. The Goal of this studys is to valuate how human ethics towards the environment, how to preserve the environment, know the educational values contained in the environment, and how it is applied in Islamic education. The research method used is a qualitative approach with the type of library research, analyzed using content methods. The results showed that Surah Al-A'raf verses 56-58 in Tafsir Al-Misbah revealed the values of environmental education, In Tafsir Ibnu Katsir revealed the values of conservation, and according to Tafsir Al-Shar'rawi revealed spiritual values. The environment is seen as a nugerah from Allah SWT to humans, which must be maintained to support the practice of worship. Surah Al-A'raf verses 56-58 in the tafsir Al-Misbah by M. Quraish Shihab can be applied in Islamic education by instilling character to form a Muslim personality who cares about the environment. This education provides an understanding that the environment is a gift that must be maintained with faith, knowledge, and self-awareness. Mutawalli Sha'rawi in tafsir Al-Sha'rawi revealed Environmental ethics can be realized through Spirituality (al-manhaj al-'Ilahi), which emphasizes the importance of associating with nature in accordance with Allah's provisions. Meanwhile, according to Ibnu Katsir, environmental ethics can be created through mutual care and responsibility. While the prohibition to damage the environment and the obligation to protect it is taught through noble moral education (akhlaq al-karimah) and worship education. Through the cultivation of these values, protecting the environment becomes a form of worship and expression of gratitude for the gifts given by Allah SWT.